2021
DOI: 10.1108/bfj-01-2020-0074
|View full text |Cite
|
Sign up to set email alerts
|

Food delivery apps (FDAs) in Asia: an exploratory study across India and the Philippines

Abstract: PurposeThis study explores and compares the reasons for or against including situational triggers on the adoption of food delivery apps (FDAs) across lesser-researched Asian countries like India and the Philippines.Design/methodology/approachThe study utilises a qualitative research methodology using focus group discussions and interviews across each country.FindingsRespondents from India highlighted the importance of convenience, aggressive discounts, app service quality, fulfilment and multiple payment optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 64 publications
(99 reference statements)
3
19
0
2
Order By: Relevance
“…Furthermore, many Asian countries such as Malaysia, Singapore and Thailand have also implemented lockdowns, resulting in many restaurants could not survive because customers could not dine in (Gursoy and Chi, 2020). For this reason, many restaurants have been forced to offer contactless services such as online food delivery (OFD) services to stay alive during the COVID-19 pandemic (Pandey et al, 2021). For instance, Statista (2021) reported that the global OFD market size had reached $111.32bn in 2020 and is expected to grow further.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, many Asian countries such as Malaysia, Singapore and Thailand have also implemented lockdowns, resulting in many restaurants could not survive because customers could not dine in (Gursoy and Chi, 2020). For this reason, many restaurants have been forced to offer contactless services such as online food delivery (OFD) services to stay alive during the COVID-19 pandemic (Pandey et al, 2021). For instance, Statista (2021) reported that the global OFD market size had reached $111.32bn in 2020 and is expected to grow further.…”
Section: Introductionmentioning
confidence: 99%
“…Extant studies have been conducted to understand factors influencing consumers' satisfaction towards and continuous intention to use OFD services (Alalwan, 2020;Cai and Leung, 2020;Cho et al, 2019;Kang and Namkung, 2019;Pandey et al, 2021;Roh and Park, 2019;Shah et al, 2020;Suhartanto et al, 2019;Troise et al, 2021;Wen et al, 2021;Xu and Huang, 2019;Yeo et al, 2017;Zhao and Bacao, 2020;Zhuang et al, 2021); the influence of OFD service quality has not been carefully examined. Most existing studies conceptualised OFD service quality based on service quality scales developed for other contexts such as m-commerce shopping (Yusra and Agus, 2020) and online self-service (Suhartanto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ). This sign seems logical as food delivery applications are becoming increasingly popular by which consumers can order food from restaurants that are located far from their workplace (Pandey et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…OFOA market share has expanded tremendously in recent years, and OFOAs are becoming increasingly competitive, particularly among the younger generation, who own smartphones and are familiar with the use of mobile apps (Saad, 2020). The conveniences provided by OFOAs—such as presenting a list of restaurants and sorting food items based on price, distance and projected delivery time, including the anticipated time for producing the food dish—and the increasing disposable income of consumers contribute to their appeal (Pandey et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%